Novel Ferrocenyl Linked Pyrazoline Analogs as Potent Antiamoebic Agents. (16th April 2015) - Parveen, Humaira; Mukhtar, Sayeed; Azam, Amir
Abstract : Some novel ferrocenyl linked pyrazoline analogs were synthesized, well characterized, and evaluated for in vitro antiamoebic activity against HM1 : IMSS strain of Entamoeba histolytica . Most of the compounds exhibited higher antiamoebic activity with the IC50 value in the range of 0.12–1.20 μM, than the reference drug metronidazole, (IC50 value of 1.78 μM). Compound9 showed the most promising antiamoebic activity (IC50 = 0.12 μM), concluding that these compounds hold immense potential to be employed as new antiamoebic agents. Also, being novel, they can be a solution to the increasing resistance that has posed a major problem globally. Abstract :